Relationship between Human Resource Management, Organizational Engagement, and Staff Work Efficiency at Suratthani Rajabhat University - ชมแก้ว, ณัฐวรา; ภู่วิทยาธร, ธนายุ; สุขศรี, นิตย์ หทัยวสีวงศ์ (Journal of Management Sciences Suratthani Rajabhat University, 2017)
The objectives of this research were: to study human resources management organizational engagement and work efficiency of staff at Suratthani Rajabhat University; and to study relationship between human resources management and organizational engagement and work efficiency of staff at Suratthani Rajabhat University. The 300 staff at Suratthani Rajabhat University were asked to answer surveys which had a reliability of .96. Data were analyzed by using frequency, percentage, mean, standard deviation, Pearson product moment correlation coefficient, Multiple regression analysis. Our research results showed overall overall human resources management, overall organizational staff engagement and overall work efficiency were all at a high level. The analysis of the relationship between human resources management and organizational engagement of the staff showed a strong positive correlation at a statistical significance level of .01 In addition, the analysis of the relationship between human resources management and work efficiency of the staff showed a weak positive correlation at a statistical significance level of .01